BOUTIQUE HOTEL INTERIOR DESIGN OF THREEHOUSE SUITES IN PATI - Adyssa, Tazkia Audrey; Atridia, Wilastrina (Arty: Jurnal Seni Rupa, 2022)
A boutique hotel is a hotel that has strong characteristics, one of which is its unique interior design style. The application of cultural elements is also an essential key for boutique hotels to attract guests. However, there is no focal element of the local culture at Treehouse Suites in Pati, Central Java. Therefore, the interior design needs to apply the elements of typical Pati decoration. This project aims to make the interior design of a boutique hotel that is convenient not only for recreational activities but also for guests traveling on business. The method used in the research is research and development. The steps include analysis of potential problems utilizing preliminary studies by means of literature review and field studies. Data were collected through observation, interviews, and documentation. This design is a design development through making design concepts and making design drawings. The results of the interior design of the Treehouse Suites Boutique Hotel bring the concept of "Back to Nature," the coastal design style, and some decorations emblematic of Pati traditions, Central Java.